Computed Tomography Image-guided Interaoperative and Stereotactic Calculation Method - Alhadidi, Tareq (British Journal of Healthcare and Medical Research, 2018)
Targeting of deep brain structure pathologies in the operation room and the concept of stereotactic that is applied on the affected zone is described. The achievement of a high accuracy using specialized stereotactic apparatus which controls the surgical tool movement inside the brain is discussed. Calculation of algorithms is necessary for operational planning included. Stereotactic system through combination of hardware-software package which specify the coordinates of surgical zone is designed. Using stereotactic method landmarks during execution of intra-operation by using CT and digital image segmentation are approved and analyzed.